2015
DOI: 10.14202/vetworld.2015.755-762
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoecological knowledge of ticks and treatment of tick-borne diseases among Maasai people in Northern Tanzania

Abstract: Aim:The aim of this study was to understand traditional knowledge of tick ecology and remedies for tick-borne diseases (TBDs) among the Maasai people in northern Tanzania.Materials and Methods:Semi-structured interviews were conducted among specific groups likely to be knowledgeable about tick ecology and TBDs in livestock among the Maasai people.Results:A total of 25 plant species belonging to 18 families were used to treat 8 different TBDs of livestock. Most of the plant species used were of Fabaceae and Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…A study by Kioko et al . [ 43 ] among Maasai in Monduli District (where we also worked) found that 56% of Maasai associated ticks with ECF. Although Maasai are very interested in foreign veterinary medicines, they are much less interested in foreign explanatory models.…”
Section: Resultsmentioning
confidence: 93%
“…A study by Kioko et al . [ 43 ] among Maasai in Monduli District (where we also worked) found that 56% of Maasai associated ticks with ECF. Although Maasai are very interested in foreign veterinary medicines, they are much less interested in foreign explanatory models.…”
Section: Resultsmentioning
confidence: 93%
“…11 Previous studies on the plant reported the antimicrobial activity of its extracts and fractions. [10][11][12] Terminalia brownii is one of the most In our study, the primary complaint of patients was intense pruritus on the legs. Some of the patients had lichenification of the skin with lichen simplex chronicus lesions on their legs as a result of excessive scratching.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Terminalia brownii has been found to have antioxidant activities and hepatoprotective properties . Previous studies on the plant reported the antimicrobial activity of its extracts and fractions . Terminalia brownii is one of the most important plants in treatment of tick‐borne diseases and is known to have antibacterial activity aganist Porphyromonas gingivalis …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations